Flavonoids with hepatoprotective activity from the leaves of Cleome viscosa L. Issue 22 (17th November 2017) - Nguyen, Tan Phat; Tran, Cong Luan; Vuong, Chi Hung; Do, Thi Hong Tuoi; Le, Tien Dung; Mai, Dinh Tri; Phan, Nhat Minh
Abstract: One new flavonol glycoside named visconoside C (1 ), together with seven known flavonol glycosides, quercetin 3-O-β-d -glucopyranoside 7-O-α-l -rhamnopyranoside (2 ), quercetin 7-O-α-l -rhamnopyranoside (3 ), astragalin (4 ), kaempferol 3- O -(4- O -acetyl)- α -l -rhamnopyranoside (5 ), kaempferol 7- O - α -l -rhamnopyranoside (6 ), kaempferitrin (7 ) and kaempferol 3- O - β -d -glucopyranoside 7- O - α -l -rhamnopyranoside (8 ) were isolated by various chromatography methods from the leaves of Cleome viscosa L. Their structures were elucidated by IR, UV, HR-ESI-MS and NMR (1D & 2D) experiments. The cytotoxicity and hepatoprotective activities using HepG2 human hepatoma cell line of1 were measured by MTT assay. At the concentration of 25 μM and 50 μM, 1 showed cytotoxic activity against HepG2 cells (cell viability was decreased to 22.2 and 23.0%, respectively, compared with doxorubicin control), while at the concentration of 100 μM, 1 showed hepatoprotective activity against CCl4 -induced hepatotoxicity on HepG2 cells (34.3%, compared with quercetin control). Abstract :